2009
DOI: 10.1111/j.1469-7580.2009.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of the red panda (Ailurus fulgens): evidence from the forelimb

Abstract: Within the order Carnivora, the phylogeny of the red panda (Ailurus fulgens) is contentious, with morphological and molecular studies supporting a wide range of possible relationships, including close ties to procyonids, ursids, mustelids and mephitids. This study provides additional morphological data, including muscle maps, for the forelimb of Ailurus, based on the dissection of four cadavers from the National Zoological Park, Washington, DC, USA. The red panda forelimb is characterized by a number of primit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(171 citation statements)
references
References 51 publications
2
124
1
15
Order By: Relevance
“…A long head originating on the scapula is the typical mammalian condition and is a feature consistent among climbers (Stalheim-Smith, 1984;Thorington et al, 1997;Fisher et al, 2009). However, the presence of additional scapular heads of the triceps as observed in badgers (Moore et al, 2013), skunks (Ercoli et al, 2014) and armadillos (Windle and Parsons, 1899) is not a feature observed in climbers, although the origin of the long head on the scapula may be broad (Harrison, 1882).…”
Section: Comparative and Functional Insightsmentioning
confidence: 94%
See 3 more Smart Citations
“…A long head originating on the scapula is the typical mammalian condition and is a feature consistent among climbers (Stalheim-Smith, 1984;Thorington et al, 1997;Fisher et al, 2009). However, the presence of additional scapular heads of the triceps as observed in badgers (Moore et al, 2013), skunks (Ercoli et al, 2014) and armadillos (Windle and Parsons, 1899) is not a feature observed in climbers, although the origin of the long head on the scapula may be broad (Harrison, 1882).…”
Section: Comparative and Functional Insightsmentioning
confidence: 94%
“…Climbing mammals have relatively less intrinsic muscle mass for elbow extension and digital flexion (Gambaryan, 1974;Taylor, 1978;Moore, 2011), and variation in relative extrinsic muscle mass is largely explained by the absence of muscles. For example, the rhomboideus capitis (and profundus) is commonly absent (Fisher et al, 2009), which may indicate less ability to protract the limb and stabilize the scapula cranially. Climbers invest in large pectoralis muscles as do scratch-diggers, but they may show relatively greater division of the pectoralis superficialis and profundus (Harrison, 1882;Julik et al, 2012) for strong adduction and increased grasping control of the forelimb during climbing.…”
Section: Comparative and Functional Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In the wild, its average lifespan is 8 to 10 yr, whereas in captivity is 13.4 yr. 10 Polycystic kidney disease (PKD) has been reported in humans 7,11,16 and in various animal species such as domestic cats 1,3,4 and dogs. 12,14 In domestic cats, the disease is more prevalent in Persian cats; 4 in dogs, it is more prevalent in terrier breeds.…”
Section: Brief Communicationmentioning
confidence: 99%